Lamento e dor: uma análise sócio-antropológica do deslocamento compulsório provocado pela construção de barragens - SANTOS, Sônia Maria Simões Barbosa Magalhães (2007)
The central idea developed in this work is that the studies carried through on the compulsory displacement provoked by the construction of dams, although mentioning the social dimension of the social suffering, do not submit that dimension to analysis. And, therefore, go round or displace the subjective sense expressed in the sorrow and pain, which is constituent to this social process. Taking as principle that the analyzed facts are socially shared and constructed, therefore carrying senses more or less lasting or more or less perceptible anyhow, publicized - that, at times, interact under the form of conflict, it is my goal to perform an analysis of the way these senses conform to three distinct and linked social situations. On the first one, the public arena, I analyze the controversy about the main classification categories for the compulsory displacement process, its contexts and main agents, trying to evidence the rhetorical construction fundamentals, in a dispute to make prevail a determined politic and social evaluation of this process. In this analysis, I emphasize the content that stabilizes itself and the intervention of one agent -the World Bank- and its role in the conformation of an expertise on the subject. In the second social situation, the academic universe, I analyze the current state of studies on the compulsory displacement, locating the main theoretical axes, in order to highlight the relation between the disciplinary and interpretative fields, mostly the hegemony of disciplinary subjects, amongst which the analysis of the suffering is not included. On the other hand, I outline that, thanks to the rigor of these analyses (many of ethnographic background), it is possible to find reference to the social suffering lived by the groups submitted to the compulsory relocating process, allowing me to fundament the hypothesis resulting of my own investigation. In the third, I analyze the process of compulsory displacement, from a research carried in Tucuruí, Pará state, Brazil, presenting the senses of social suffering evocated by those who lived it, pointing out: a) the absence of parameters to evaluate the consequences of the process lived, not only because it is an unusual situation as because the undertaking itself unchains other local and regional transformations that are not given a priori; b) the incessant search of a way to replace a situation lost or desired, that can be seen in public forums (assemblies, meetings, encounters), considered here as "sorrow forums", because they are, concomitantly, a place of public claim and spaces of encounter with their own history and, consequently, spaces for reminding and stating losses; c) the irreversible character, that lines the construction of social suffering. Finally, I try to show the constraints, above all economical, that are verified in the passing from the suffering dimension to the public arena.